Strengthened primary health care for universal health coverage through improved community diagnosis and management of pneumonia in Zimbabwe - Portia Manangazira; Itai Rusike; Mandy Mathias; Tjedu Moyo; Moreblessing Chibaya; Joshua Panashe Rusike (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2023)
Pneumonia is the world's leading infectious killer, claiming the lives of an estimated 2.5 million including more than 670,000 children under five years and 1.2 million adults in 2019 alone. Caused largely by viruses, and bacteria, COVID-19 also increased the pneumonia burden, while environmental factors, poor hygiene, sanitation and underlying conditions including malnutrition predispose. The latter translates into a considerable pneumonia burden that is preventable, provided the requisite provisions are made for community-level protection such as environmental management, water, sanitation and hygiene; and key persons are informed and educated on preventive and therapeutic measures, especially what to look for and what to do at home while seeking medical attention. Irked by the high numbers of under-five deaths against a background of limited case management caused by the system-wide collapse of the health services in the country, we sought to utilize the opportunity offered by world pneumonia day 2022 to go down to the community and elicit both the disease burden and strategies to address pneumonia that can be applied within the home and community. We also wanted to hear from the community their experiences with and functionality of the referral system. This paper presents the findings, challenges and suggestions for improving primary healthcare implementation to address the current high morbidity and mortality attributable to pneumonia. We found the Goromonzi community to be literate in many health issues but need more information and training to better manage pneumonia. They were knowledgeable about pneumonia, tuberculosis, and the recent COVID-19 through their interactions with the local clinic staff, the media, and interpersonal communication. Some were members of the health center committee or were village health workers or local leaders. We had limitations of resources and time for a detailed study, but conclude that the community visited had a sound understanding of health, primary health care and pneumonia, but lacked the comprehensive education and support to effectively manage pneumonia at home. More work needs to be done to quantify the pneumonia burden, the contribution of each intervention, (environment, vaccination, exclusive breastfeeding, safe water, sanitation, hand hygiene, reduced smoke and case management) the benefit of home and community management alongside an effective referral chain.